Absorbable Fixation Devices for Pediatric Craniomaxillofacial Trauma: A Systematic Review of the Literature. Issue 3 (September 2019) - Lopez, Joseph; Siegel, Nicholas; Reategui, Alvaro; Faateh, Muhammad; Manson, Paul N.; Redett, Richard J.
Abstract : Background: The purpose of this study was to investigate surgical outcomes with the use of resorbable plating systems for the repair of craniomaxillofacial trauma in the pediatric population. Methods: A systematic review of the literature was performed. A descriptive analysis, operative technical data, outcomes, and postoperative complications with the use of absorbable plating systems for craniomaxillofacial trauma were included. Results: The systematic literature review identified 1264 abstracts, of which only 19 met inclusion criteria. From these 19 studies, 312 clinical cases with 443 facial fractures that were treated with absorbable fixation systems were extracted for analysis. The review identified only level III/IV ( n = 17) and level V ( n = 2) studies. Minor and major complications were rare, occurring in 5.45 percent ( n = 17) and 3.21 percent ( n = 10) of cases, respectively. The most common complications were surgical-site infections ( n = 4) and plate extrusion ( n = 4). Conclusions: This report is, to the authors' knowledge, one of the first comprehensive reports on the use of absorbable plating systems for pediatric craniomaxillofacial trauma. Their analysis suggests that the use of absorbable fixation devices for pediatric craniomaxillofacial trauma is relatively safe, with a low-risk profile. Outcome studies with longer follow-up periods specifically investigating facial growth, reoperation rates, standardized surgical outcome metrics, and cost are necessary to effectively compare these fixation devices to titanium alternatives for craniomaxillofacial trauma.